Eksplorasi dalam rekaan pola fesyen dengan mengurangkan pembaziran fabrik - Nor Liza, Binti Sedon@M.Dom (Universiti Malaysia Sarawak (UNIMAS), 2008)
This research is conducted to identifo and find a solution to design an innovative pattern which can reduce fabric remanents. The design are focuses on Evening Wear, Casual Wear and office Wear with the application of natural fabric such as cotton, linen and silk. Darts, rubber and gathers techniques are applied to reduce fabric waste on the pattern layout.